Responses of Noccaea caerulescens and Lupinus albus in trace elements-contaminated soils - Martínez-Alcalá, Isabel (Plant physiology and biochemistry : PPB, 2013)
Crown Copyright © 2013. Published by Elsevier Masson SAS. All rights reserved.